Mass ion separation in the plasma flow moved along the toroidal magnetic field - Sokolenko, E.N.; Khizhnyak, N.A. (Вопросы атомной науки и техники, 2000)
The motion of rarefied (one particle approximation) and dense (a drift approximation) plasma flows in the toroidal solenoid magnetic field with the intensity of H = (0, H₀ r₀/r, 0), is considered. It is shown that the base parameter characterizing separate particle paths is a = (Mv₀c)/(eH₀r₀), where v₀ is the particle velocity parallel to the magnetic field on the input of a toroidal part of the magnetocircuit, r₀ is the radius of magnetic field line curvature of this part. The role of short circuit currents in moving dense plasma flows and their effect on particle paths taking into account, selfconsistent electrical polarized field is discussed. The possibility of using such fields for mass ion plasma flow separation both in the rarefied plasma and dense ones is revealed. It is shown, that the presence of the short circuits influences essentially on the radial particle movement, but the axial displacement even in the dense plasma and irrespective of conductance of the short circuit is determined by particle masses. This gives the possibility to expect ion mass separation in the toroidal solenoid magnetic field would be preserved also in powerful ion flows. The effect of electron temperature and electron-ion collisions on separation properties of the curved magnetic field is discussed.